Atmospheric CO2 Exchange of a Small Mountain Lake: Limitations of Eddy Covariance and Boundary Layer Modeling Methods in Complex Terrain. Issue 7 (22nd July 2021) - Scholz, K.; Ejarque, E.; Hammerle, A.; Kainz, M.; Schelker, J.; Wohlfahrt, G.
Abstract: Lakes receive and transform significant amounts of terrestrial carbon and are often considered a source of atmospheric carbon dioxide (CO2 ). Yet, continuous direct measurements of lake‐atmosphere CO2 exchange with high temporal resolution are sparse. In this study, we measured the CO2 exchange of a mountain lake in the eastern Austrian Alps continuously for one year using the eddy covariance (EC) and the boundary layer model (BLM) approaches. Results from both the EC and the BLM methods indicated the lake to be a small source of atmospheric CO2 with highest emissions in fall. EC flux measurements were affected by low‐frequency contributions especially during low wind conditions. The CO2 concentration gradient at the air‐water interface decreased during night‐time due to an increase in atmospheric CO2 above the lake, likely caused by cold and CO2 ‐rich air draining from the surrounding land. Consequently, BLM fluxes were lower during night‐time than during daytime. This diel pattern was lacking in the EC flux measurements because the EC instruments deployed at the shore of the lake did not capture low nocturnal lake CO2 fluxes due to the local wind regime. Overall, this study illustrates the effect of the surrounding landscape on lake‐atmosphere flux measurements. We conclude that estimating CO2 evasion from lakes situated in complex topography needs to explicitly account for biases in EC flux measurements caused by low‐frequency contributions and local wind regimes. Plain Language Summary: Lakes and rivers are an important link in the global carbon cycle transporting carbon from the land to the oceans. However, part of the carbon entering the water is stored in lake sediments or released from the water into the atmosphere as carbon dioxide (CO2 ). Therefore, lakes are considered important sources of atmospheric CO2, yet continuous direct measurements of this water‐air CO2 exchange are sparse. In this study, we used two different methods to measure the CO2 exchange of a small lake in the Austrian Alps for an entire year. We found that during the ice covered period, in spring, and in summer the CO2 exchange between lake and air was small. In fall, the lake released CO2 at higher rates. Overall, the lake was only a small source of CO2 . We also found significant differences in the results of the two measuring methods. Those results demonstrated that measurements of lake‐atmosphere CO2 exchange are complex and—especially if the lake is small and situated in a mountainous landscape—the surrounding land can influence the measurements. Key Points: We estimated the carbon dioxide (CO2 ) exchange of a small mountain lake using the eddy covariance and the boundary layer model approaches CO2 fluxes were small and variable, and the variation in local atmospheric CO2 concentration was an important driver of lake CO2 exchange The study demonstrates that the influence of the surrounding land has to be considered in lake‐atmosphere flux measurements